Conserving Threatened and Endemic Fruit Bats in Isolated Forest Patches in Cebu with notes on new records and rediscoveries - Pagunutalan, Lisa Marie J.; Jakosalem, Philip Godfrey C. (Silliman Journal, 2023)
A survey of fruit bats in five isolated forest patches (Alcoy forest, Dalaguete forest, Tabunan forest, Mt. Lantoy in Argao, and •Carmen forest) in Cebu island, Philip-pines was conducted from February 2001 to January 2004 using mist nets for small to medium sized fruit bats and direct roost observations for flying foxes. A total of twelve species of fruit bats composed of six threatened species, six en-demic species and four new island records (Golden-crowned flying fox Acerodon jubatus, Harpy Fruit Bat Harpyrbnycteris whiteheadi, Philippine Pygmy fruit bat Haplanyrteris &cher!, and Large flying fox Pteropus vampyrus) were documented bringing the total record of Cebu to 13 species of fruit bats. Roosting colonies of flying foxes monitored over two years have shown marked reduction in roost counts indicating increased disturbance. Despite the relative difference in forest sizes, the smaller forest patch of Dalaguete recorded the highest number of fruit bats as compared to the larger forest in Alcoy. However, bat species (Harpy fruit bat and Philippine Pygmy fruit bat) more intolerant to habitat disturbances were captured only in Alcoy. Hunting, cutting of trees for charcoal, and habitat loss were among the major threats observed.